2010
DOI: 10.3851/imp1646
|View full text |Cite
|
Sign up to set email alerts
|

Z-FA-FMK as a novel potent inhibitor of reovirus pathogenesis and oncolysis in vivo

Abstract: Z-FA-FMK is a very effective viral inhibitor that can prevent reovirus replication in vitro and reovirus-mediated myocarditis, as well as reovirus-mediated oncolysis, in vivo. A potential application of this drug for inhibition of reovirus infection is suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Another study demonstrated that chestnut and quebracho wood extracts containing tannin show antiviral activity against avian reovirus and metapneumovirus (41). The dipeptide, benzyloxycarbonyl-Phe-Ala-fluoromethyl ketone (Z-FA-FMK), is a novel potent inhibitor of reovirus pathogenesis and oncolysis in vivo (42). These drugs act by inhibiting reovirus replication and adsorption, but their potential side-effects are yet to be clinically evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Another study demonstrated that chestnut and quebracho wood extracts containing tannin show antiviral activity against avian reovirus and metapneumovirus (41). The dipeptide, benzyloxycarbonyl-Phe-Ala-fluoromethyl ketone (Z-FA-FMK), is a novel potent inhibitor of reovirus pathogenesis and oncolysis in vivo (42). These drugs act by inhibiting reovirus replication and adsorption, but their potential side-effects are yet to be clinically evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Reovirusinduced myocarditis is not immune-mediated, and infection will cause myocarditic lesions in nude mice or mice lacking B-and T-cells [47,76]. Reovirus-induced cardiac damage occurs as a consequence virus-induced apoptosis of myocytes, and disease does not occur in mice lacking caspase 3 or in WT mice treated with inhibitors of apoptosis [77][78][79][80]. Comparisons of reovirus strains that vary in the capacity to cause myocarditis have identified phenotypic and genetic differences that correlate with myocarditic potential.…”
Section: Plos Pathogensmentioning
confidence: 99%
“…Reovirus-induced myocarditis is not immune-mediated, and infection will cause myocarditic lesions in nude mice or mice lacking B- and T-cells [42, 63]. Reovirus-induced cardiac damage occurs as a consequence virus-induced apoptosis of myocytes, and disease does not occur in mice lacking caspase 3 or in WT mice treated with inhibitors of apoptosis [6467]. Comparisons of reovirus strains that vary in the capacity to cause myocarditis have identified phenotypic and genetic differences that correlate with myocarditic potential.…”
Section: Discussionmentioning
confidence: 99%